(untitled) (Bangladesh Journal of Neuroscience, 2014)
Introduction: The parameters of fontanelle can be very reliable and helpful source to assess the internal status of hydrocephalus in early childhood. Methods and Materials: We have studied the parameters of 69 patients of hydrocephalus in early childhood to assess the status of hydrocephalus. All the patients - who were admitted in the Bangabandhu Sheikh Mujib Medical University from January 2002 to December 2003. Results: All patients were evaluated clinically as well as with imaging study. The age range was from newborn to 12 months. There was male preponderance; male to female ratio was 2.6:1. Clinical evaluation of head and face showed 97.10% patients had open anterior fontanelle, 88.41% had apparent large head, 59.04% had presence of sunset sign. Analysis of anterior fontanelle showed 66.67% had bulged fontanelle, 30.43% had flat fontanelle and 2.90% had concave fontanelle. Evaluation of the clinical status of posterior fontanelle revealed that 23.19% had open posterior fontanelle. Among them 15.94% had bulged and 7.25% had flat fontanelle. Conclusion: By analyzing the result we found that clinical evaluation of fontanelle gives good guidance to assess the status of hydrocephalus in early childhood. Bangladesh Journal of Neuroscience 2011; Vol. 27 (2) : 83-86 DOI: http://dx.doi.org/10.3329/bjn.v27i2.17574